What's New in Immunology? - Armstrong, W. D. (1975)
Since 1950, immunology has developed with such rapidity as an interdisciplinary science that even those within the field have difficulty keeping adequately informed. For this reason it is important that those who are closer to the subject, wherever possible, apply recent advances to the practice of medicine in general and primary care in particular. This paper describes a limited number of recent advances in the field of cellular immunology and immunodeficiency diseases. Above all, it attempts to relate the practical significance of these discoveries to the care of the patient by the primary care physician.